Simulating the influence of microclimatic design on mitigating the urban heat island effect in the Hangzhou metropolitan area of China - Shen, T.; Chow, D.H.C.; Darkwa, Jo (Oxford University Press, 2016)
There are many indications that Urban Heat Island (UHI) is a significant contributor to the increased emission of greenhouse gases due to the increase in energy consumption for cooling during summer. Hangzhou is currently the second hottest city in China, and this paper investigates how the West Lake and the Xixi Wetland areas in the city act as passive thermal comfort systems in improving the outdoor built environment and mitigating UHI effect. Through using ENVI-met, this research evaluates the most effective development scenarios of West Lake and Xixi Wetland area for reliving UHI effect. The energy consumptions for cooling in a typical office building located close to the West Lake and Xixi Wetland under different development scenarios of these two ecological resources are then also compared. It was shown that the average atmosphere temperature and urban heat intensity in urban area increased by more than 0.5°C if the West Lake and Xixi Wetland are both transformed to building construction areas. Moreover, the cooling demand of a typical office building in summer would increase by 10.8% due to ambient temperature increasing by 0.5°C.